Longitudinal quantification of aqueous flare and cells in Vogt–Koyanagi–Harada disease. Issue 2 (26th October 2007) - Fang, W; Zhou, H; Yang, P; Huang, X; Wang, L; Kijlstra, A
Abstract : Aims: To quantitatively evaluate the changes of aqueous flare and cells in eyes with Vogt–Koyanagi–Harada (VKH) disease. Methods: This prospective study included 35 initial-onset VKH patients (70 eyes) and 46 recurrent VKH patients (92 eyes) following immunotherapy. Aqueous flare and cells were quantified using the laser flare-cell meter before treatment, 2 weeks, 1, 3, 6 and 9 months after treatment. Results: Before treatment, mean aqueous flare (ph/ms) in initial-onset and recurrent VKH eyes were 8.1 (SD 4.1) vs 43.6 (20.7) (p = 0.000). Following treatment, recurrent VKH eyes showed a significantly higher flare value than initial-onset VKH eyes at 2 weeks, 1, 3 and 6 months. Prior to treatment, mean cell counts (cells/0.5 mm3 ) in initial-onset and recurrent VKH eyes were 2.0 (1.9) vs 39.4 (23.1) (p = 0.000). Following treatment, recurrent VKH eyes showed significantly higher cell counts than initial-onset VKH eyes at 2 weeks, 1 and 3 months. Conclusions: Our study shows that recurrent VKH patients displayed a more striking and long-lasting breakdown of the BAB and more severe inflammation than initial-onset VKH patients. Our study also indicates that the disruption of BAB lasted longer than aqueous cells either in initial-onset or in recurrent VKH patients.